2021
DOI: 10.1101/2021.02.08.430229
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

C1q binding to surface-bound IgG is stabilized by C1r2s2proteases

Abstract: Complement is an important effector mechanism for antibody-mediated clearance of infections and tumor cells. Upon binding to target cells, the antibody's constant (Fc) domain recruits complement component C1 to initiate a proteolytic cascade that generates lytic pores and stimulates phagocytosis. The C1 complex (C1qr2s2) consists of the large recognition protein C1q and a heterotetramer of proteases C1r and C1s (C1r2s2). While interactions between C1 and IgG-Fc's are believed to be mediated by the globular hea… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 91 publications
0
19
0
Order By: Relevance
“…Like the pneumococcal capsule, WTA is an abundant and exposed glycopolymer on the cell wall of S. aureus (76). For mAbs targeting WTA, we recently observed that WT IgG1 and IgG3 mAbs could induce complement activation and downstream phagocytosis in the absence of Fc-Fc enhancing mutations (75). At present it is unclear why these WT anti-capsular antibodies showed a poor capacity to induce complement activation on S. pneumoniae.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Like the pneumococcal capsule, WTA is an abundant and exposed glycopolymer on the cell wall of S. aureus (76). For mAbs targeting WTA, we recently observed that WT IgG1 and IgG3 mAbs could induce complement activation and downstream phagocytosis in the absence of Fc-Fc enhancing mutations (75). At present it is unclear why these WT anti-capsular antibodies showed a poor capacity to induce complement activation on S. pneumoniae.…”
Section: Discussionmentioning
confidence: 99%
“…For the anti-capsular antibodies included in this study, we showed that monoclonal IgGs had a poor capacity to activate complement when expressed with wild-type Fc domains. This in sharp contrast to monoclonal IgGs recognizing wall teichoic acid (WTA) on the surface of S. aureus (75). Like the pneumococcal capsule, WTA is an abundant and exposed glycopolymer on the cell wall of S. aureus (76).…”
Section: Discussionmentioning
confidence: 99%
“…The result indicated a significantly higher number of C1 accumulated on the IgG-covered membranes than C1q (Fig. 2), explaining the slower off rate of C1 than C1q on the IgG-immobilized surface shown by the previous surface plasmon resonance experiment [21]. It is supposed that the binding of the IgG hexameric ring suppresses motional freedom of the C1q globular heads.…”
Section: Comparing Dynamic Interactions Of Igg Assemblages With C1 and C1q On Antigenincorporated Membranesmentioning
confidence: 70%
“…Processing of test results. Results obtained by measurement of reference individuals were directly used for establishment of reference intervals, if the relative bias between the means of measured values of reference materials obtained by the analytical systems and the assigned target values of reference materials meet the desirable speci cation for inaccuracy of biologic variation [17] .…”
Section: Laboratory Analysismentioning
confidence: 99%
“…Complement C1q is an important component of complement C1. [17] Studies have shown that the absence of serum complement C1q (including lack of component and functional disorder) will cause the body's immune complex deposition in tissue, causing immune complex diseases, such as SLE, glomerulonephritis[18], etc. It is found that NGAL is closely related to the occurrence of chronic kidney disease and can be an important marker for early renal injury [13,19].…”
Section: Introducementioning
confidence: 99%